2022
DOI: 10.3390/ijerph192215245
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Food Security Status and Psychological Distress and Loneliness among Full-Time Undergraduate Students at a Minority-Serving Institution

Abstract: Little is known about the relationship of food security (FS) status with mental health among students at minority-serving institutions. We aimed to elucidate the association of FS status with psychological distress and loneliness among full-time undergraduate students at a minority-serving institution. We used data from the National Collegiate Health Assessment III (n = 441). To assess FS, students responded to the USDA 6-item short form (range: 0–6) and responses were categorized as high (0), marginal (1) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…This finding highlights the need for particular attention to be given to student parents due to the negative impacts of food insecurity on the students themselves as well as on their children [52][53][54]. Parents experiencing food insecurity may compromise their own nutritional intake to preserve the adequacy of their children's diets [55][56][57], which can impact their own academic achievement, physical health, mental well-being, and social operations [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…This finding highlights the need for particular attention to be given to student parents due to the negative impacts of food insecurity on the students themselves as well as on their children [52][53][54]. Parents experiencing food insecurity may compromise their own nutritional intake to preserve the adequacy of their children's diets [55][56][57], which can impact their own academic achievement, physical health, mental well-being, and social operations [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…↓ Executive function 3. ↑ ACEs Guzman et al., 2022 [ 95 ] 441 San Diego State University Female: 76.7% Non-White: 63.5% FI: 33.8% 6-item 1. Psychological distress 2.…”
Section: Fi and Psychosocial Health Outcomesmentioning
confidence: 99%
“…Studies using the Diener Flourishing Scale found that college students with FI had significantly higher psychological distress than their FS counterparts [ 30 , 91 , 92 ]. Psychological well-being was also assessed in select studies through the Kessler-6 Scale [ 93 ] or the WHO Five Factor Well-being Index [ 94 ], in which individuals experiencing FI had lower overall psychological well-being than FS peers [ 91 , 92 , [94] , [95] , [96] , [97] , [98] ]. A more general mental health assessment through the Centers for Disease Control and Prevention Healthy Days Core Module found that college students with FI were at an increased risk for poor mental health status [ [99] , [100] , [101] ].…”
Section: Fi and Psychosocial Health Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Bank (1996) defines food security as “when all people, at all times, have physical and economic access to sufficient safe and nutritious food that meets their dietary needs and food preferences for an active and healthy life.” While a significant issue in low- and middle-income countries such as India (George & McKay, 2019), food security is also a problem for many high-income countries (Loopstra, 2018). Loneliness has also been related to food insecurity at different ages (Guzman et al, 2022; Howe-Burris et al, 2022), with home food delivery programs such as Meals on Wheels in the US being associated with decreases in loneliness among older adults (Ross et al, 2022; Thomas et al, 2016; Wright et al, 2015). Poverty among those who work is high in several parts of Asia, including India and this is likely to be heightened in the case of older adults (Economic and Social Commission for Asia and the Pacific, 2022).…”
Section: Introductionmentioning
confidence: 99%